A „Nagy-Debrecen”-gondolat megszületése - Lakner, Lajos (Studia Litteraria, 2021)
From the 1870s onwards, Debrecen became a regional economic, commercial and educational center. By the end of the century, the notion of Debrecen being the safeguard of national and literary culture became popular, preserved by the pure Hungarian culture of the city’s middle class. At this time, however, this prominence in national policy was only the aspiration of the literary elite of Debrecen. In 1909, the notion of Nagy-Debrecen (Great Debrecen) became a political category, meaning the real capital of Hungary was not Budapest, but Debrecen. It was particularly important that the concept was introduced by Viktor Rákosi, editor of Budapesti Hírlap, an official government newspaper, which made it seem that this was not only the aspiration of the local elite, but an officially endorsed notion. e study is concerned with exploring the origins of the Nagy Debrecen notion and its layers of meaning, and showcases how this late 19th century concept became the basis for the Nagydebrecen (Great Debrecen) notion of the 1920s, put forth by Kuno Klebelsberg.